Trends and variability in weather and atmospheric deposition at UK Environmental Change Network sites (1993–2012). (September 2016) - Monteith, Don; Henrys, Peter; Banin, Lindsay; Smith, Ron; Morecroft, Mike; Scott, Tony; Andrews, Chris; Beaumont, Deborah; Benham, Sue; Bowmaker, Victoria; Corbett, Stuart; Dick, Jan; et al.
Abstract: We characterised temporal trends and variability in key indicators of climate and atmospheric deposition chemistry at the twelve terrestrial UK Environmental Change Network (ECN) sites over the first two decades of ECN monitoring (1993–2012) using various statistical approaches. Mean air temperatures for the monitoring period were approximately 0.7 °C higher than those modelled for 1961–1990, but there was little evidence for significant change in air temperature over either the full monthly records or within individual seasons. Some upland ECN sites, however, warmed significantly over the first decade before cooling in the second. Summers at most sites became progressively wetter, and extremes in daily rainfall increased in magnitude. Average wind speeds in winter and spring declined at the majority of sites. Directional trends in summer precipitation could be linked to an atypically prolonged negative deviation in the summer North Atlantic Oscillation (NAO) Index. Several aspects of air quality improved markedly. Concentrations and fluxes of sulphate in precipitation declined significantly and substantially across the network, particularly during the earlier years and at the most polluted sites in the south and east. Precipitation concentrations of nitrate and ammonium, and atmospheric concentrations of nitrogen dioxide also decreased at most sites. There was less evidence for reductions in the loads of wet deposited nitrogen species, while trends in atmospheric ammonia concentration varied in direction and strength between sites. Reductions in acid deposition are likely to account for widespread gradual increases in the pH of soil water at ECN sites, representing partial recovery from acidification. Overall, therefore, ECN sites have experienced marked changes in atmospheric chemistry and weather regimes over the last two decades that might be expected to have exerted detectable effects on ecosystem structure and function. While the downward trend in acid deposition is unlikely to be reversed, it is too early to conclude whether the trend towards wetter summers simply represents a phase in a multi-decadal cycle, or is indicative of a more directional shift in climate. Conversely, the first two decades of ECN now provide a relatively stable long-term baseline with respect to air temperature, against which effects of anticipated future warming on these ecosystems should be able to be assessed robustly.